Analysis of Shelters for Floods Disaster Management in Central Klaten and South Klaten Klaten District - Andriana, Pramesthy Inta; Sari, Dewi Novita; Fatmawati, Hanifah (Universitas Muhammadiyah Surakarta, 2024)
Purpose: The goals of this research are (1) to analyze the distribution of shelter or houses that suitable temporary shelters during disaster and (2) examine the capacity and supportability the area for the temporarry shelter during disaster. Methodology: The research methodology includedm followed by a descriptive quantitive approach and analysis of the carrying capacity of settlements. Results: The findings indicate a clustered distribution pattern of shelter in South Klaten sub-district (NNR value of 0.366222 and a z-score of - 18.900393) in Central Klaten sub-district ( NNR of 0.468301 with a z-score of -15. The settlement carrying capacity value in both sub-districts are greater than 1, suggesting they can accommodate additional populations of 27,500 and 4,205 people, respectively. Applications/Originality/Value: Distribution Pattern, Hydrometeorological Disaster, Nearest Neighbourhood Analyze, Shelter, Supportability.